IPO Banks : pitch, selection and mandate - Espinasse, Philippe; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Former banker Philippe Espinasse, offers advice for the interview, selection and appointment of lead banks, as well as for the execution of an IPO. The book includes case studies from around the world and explains negotiation techniques through which issuers can save considerable time, effort and costs, and also limit their potential liabilities.
Keywords: Management